Key stakeholders and platforms/networks in food system transformation in Vietnam in 2022 - Huynh Thi Thanh Tuyen; Pham Thi, Huong Mai; Duong, Thanh Thi; Pittore, Katherine H.; Herens, Marion C. (2022)
The stakeholder identification is initiated under the SHiFT initiative to identify with whom the project needs to engage with in order to achieve food system transformations. It brings together all the stakeholders working on food systems issues in a so-called ‘living’ database that can be used to quickly identify potential stakeholders in each of the SHIFT focal countries. Understanding, engaging and capacitating the different food system stakeholders will provide diverse perspectives to foster collaborations to leverage transformative actions across the system to improve outcomes. This stakeholder identification is a first step to build an understanding who (people and institutions) is engaged with food system issues at different governance levels, including public and private actors, those working in formal and informal sectors at national, regional and local government level. In addition, the SHiFT country engagement approach is looking to connect with and strengthen existing stakeholder (coordination) mechanisms or platforms in the domain of food system transformation rather than establish new collaborative structures. Applying a stakeholder platform mapping tool to detect (coordination) structures engaged around food system issues existing platforms and networks are identified.